Lekcja pejzażu (według) Adama Chmielowskiego – świętego Brata Alberta - Pyczek, Wacław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The presented study is an attempt at recgnition and description of basic aesthetic tendencies and purely artistic qualities as well as metaphisical perspectives determining the character od Adam Chmielowski’s landscapes. The realm of artictic activity of the Polish painter is presented against the context of landscape painting history – both Polish and European. The author of the current article appreciates the role of an important reference system – the realm of spirit expressed in various artistic gestures which constitutes a secret element of Chmielowski’s work.